Factors Influencing Organic Food Purchase Intentions: Mediating Attitudes - Kris Amelia Widjaja; Lina Salim; Ho Shu-Hsun (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2025)
This study seeks to investigate the influence of health consciousness, environmental awareness, subjective norms, food safety awareness, and availability on the intention to purchase organic food, with attitudes towards organic food as a mediating factor. The research employs an online survey method, collecting data from 386 respondents via Google Forms. Data analysis was conducted using SPSS 27 and PLS-SEM through SmartPLS4 software. The analysis reveals that attitudes towards organic food significantly impact purchase intentions. Specifically, attitudes fully mediate the relationship between food safety awareness and purchase intention and partially mediate the relationships between subjective norms, availability, and purchase intention. However, health consciousness and environmental awareness do not directly affect purchase intention but may have an indirect impact through attitudes towards organic food. This work contributes to the understanding of how various factors influence organic food purchase intentions, emphasizing the mediating role of attitudes. The findings indicate that enhancing consumer attitudes towards organic food can boost purchase intentions. Organizations should focus on marketing the benefits of organic products and ensuring their availability through diverse channels. This study's limitation includes a sample that may not fully represent diverse consumer behaviors regarding organic products. Future research should explore a broader range of demographic factors and different organic product categories to enhance understanding of purchase intentions.